OLAHRAGA DI LINGKUNGAN INDOOR PADA MALAM HARI MENGHASILKAN RASIO KERINGAT LEBIH BANYAK DIBANDINGKAN PAGI HARI - Mita Andriana, Laily; Ashadi, Kunjung; Sandi, I Nengah (Sport and Fitness Journal, 2019)
Background: Physical exercise cannot be separated with body sweating, which is one of effort the body to maintain the homeostatic and thermoregulation. the factor of sweat rate is environment condition, for examples are room temperature and relative humidity. Aim: Compare physical exercise in two different environmental conditions, including at night and in the morning to the sweat rate. Method: The quantitative research design with descriptive design uses a one shot case study. Using as many as 40 male students divided into four groups. Result: To find out the differences between the two groups, this study used independent samples t-test. The group continuous running activity in the morning and at night has an average sweat rate as much as 0,49 liter ± 0,28 and 0,62 liter ± 0,31 with the value of (p > 0,05). The group cycing with HIIT activity in the morning and at night has an average sweat rate as much as 0,34 liter ± 0,177 and 0.42 liter ± 0,176 with the value of (p > 0,05). Conclusion: The average sweat rate of night physical exercise is more than the average sweat rate in the morning, even though there is no significant difference between both. Keywords: Relative humidity, night physical exercise, morning physical exercise, sweat rate, thermoregulation